Biosafety in the use of pesticides in the perception of farmers in the District of Cuncas, Barro - Ceará: Physical and Environmental Health (Research, Society and Development, 2021)
Among the activities developed by humans, the practice of agriculture has been going on for over 10,000 years, and is one of the oldest known. Technological innovations in this area have brought about great changes, and the implementation of new cultivation techniques, such as the intensive use of pesticides. The use of pesticides is increasingly present in the daily lives of farmers, which ends up triggering a situation of dependence, due to the need for pest control in crops. Given the above, the objective of the work was to identify the level of knowledge of farmers in the District of Cuncas, Barro - CE on the risks of the use of pesticides. Data collection involved the application of structured questionnaires between January and February 2019. The results showed that there is an indiscriminate use of pesticides by a large part of the interviewees. It was observed that the vast majority of farmers do not know how to identify the toxicological classification of pesticides. High dosages of pesticides are used by farmers. Empty packaging is usually discarded incorrectly in the environment or burned in the open. Only 10% of farmers reported taking care to return the packaging. Farmers experienced symptoms of intoxication, such as headache, dizziness and nausea. It is concluded that farmers have, in general, a low perception of risk regarding the harmful effects of the use of pesticides, making it necessary to adopt measures that provide technical monitoring and minimize the impacts caused to human and environmental integrity.